Digital Transformation in MSMEs: Challenges and Opportunities in Technology Management - Hendrawan, Satya Arisena; Afdhal Chatra; Nurul Iman; Soemarno Hidayatullah; Degdo Suprayitno (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to examine the challenges and opportunities in the digital transformation of MSMEs, as well as effective technology management strategies. In the digital era, MSMEs face various challenges such as limited financial and human resources, inadequate digital infrastructure, and lack of knowledge and awareness about technology. Nevertheless, digital transformation also offers significant opportunities for MSMEs, including improved operational efficiency, access to broader markets, and the ability to analyze data for better decision-making. Through a qualitative approach with literature review, this research finds that effective technology management strategies are crucial for the successful digital transformation of MSMEs. These strategies include developing a technology strategic plan aligned with business goals, selecting and integrating appropriate systems, and training and developing employees' skills. The proper implementation of digital technology can help MSMEs automate business processes, reduce operational costs, and enhance productivity and innovation. The study concludes that digital transformation is not just about adopting technology but also about changing work processes and mindset to create sustainable added value for MSMEs. With adequate support and well-planned strategies, MSMEs can overcome challenges and leverage digital opportunities for business growth and sustainability.